A Comparative Evaluation of Cross Linked Starch Urea-A New Polymer and Other Known Polymers for Controlled Release of Glipizide - Chowdary, K.P.R.; Vijaya Deepthi, K. (Asian Journal of Chemistry, 2010)
The objective of the present investigation is to synthesize cross-linked starch-urea, a new starch based polymer and to evalate its application for controlled release of glipizide. The release retarding and rate controlling efficiency of cross-linked starch-urea was also compared with that of other known polymers. Starch-urea (carbamate) was prepared by gelatinizing potato starch in the presence of urea. The starch-urea was then cross linked treatment with calcium chloride to result in cross-linked starch-urea. Matrix tablets each containing 10 mg of glipizide were formulated employing cross-linked starch-urea in different concentrations in the formula and other polymers such as methyl cellulose (MC), hydroxy propyl methyl cellulose (HPMC, K15M), sodium carboxy methyl cellulose (sodium CMC) and sodium alginate (SA) at 1:1 ratio of drug:polymer by wet granulation method and the tablets were evaluated. Glipizide release from the matrix tablets formulated employing cross-linked starch-urea was slow, spread over 24 h and depended on the concentration of cross-linked starch-urea polymer in the tablets. Non-Fickain diffusion was the drug release mechanism from these matrix tablets. Matrix tablets (F2) formulated employing 50 % cross-linked starch-urea > sodium CMC > sodium alginate > methyl cellulose. Cross-linked starch-urea was found to be a better release-retarding polymer than sodium alginate, sodium CMC and methyl cellulose. Cross linked starch-urea and HPMC, K15M were found more suitable for controlled release application. Glipizide CR tablets for once-a-day (24 h) administration could be designed employing cross-linked starch-urea.